The capital gains lock-in effect on earnings quality - Feng, Fan (2019)
The taxation of realized capital gains creates a lock-in effect. I examine how the capital gains lock-in of mutual funds affects their portfolio firms’ earnings quality. I hypothesize and find that unrealized capital gains of mutual funds are positively associated with the earnings quality of their portfolio firms. Consistent with tax-induced lock-in, the effect of unrealized capital gains is more pronounced for tax-sensitive mutual funds than for tax-insensitive mutual funds. My findings are robust to five alternative categories of earnings quality measures. Moreover, the positive effect of capital gains lock-in on earning quality is stronger during periods of high capital gain tax and when the mutual fund holdings are highly concentrated. In sum, my findings suggest that locked-in mutual funds improve their portfolio firms’ earnings quality through more monitoring.